THE USE OF BOARD RACE LANGUAGE GAME TO IMPROVE STUDENTS’ SPEAKING ABILITY - Maisaroh Afidah; Nunung Anugrawati; Eka Prabawati Rum (English Language Teaching Methodology, 2021)
The objective of this research was to found out whether or not the use of board race language game can improve students’ speaking ability at SMA Negeri 9 Makassar. The researcher used a pre-experimental research as design method and gave pre-test, treatment and post-test. The sample of this research was XI MIA 5 class of SMA Negeri 9 Makassar which consisted of 30 students. The sample was taken by used Purposive Sampling Technique. Based on the result, the mean score of students’ pronunciation and vocabulary before and after the treatment improved. The students’ pronunciation scores from 58.14 to be 84.25 and the students’ vocabulary scores from 57.69 to be 87.29. The differences mean score of pre-test was higher than pre-test. The value of T-test in pronunciation 18.38>2.04 and the value of t-test in vocabulary was 20.57>2.04. The alternative hypothesis is accepted and the null hypothesis is rejected. It means that using of board race games as a teaching technique in teaching speaking can improve students’ speaking ability at eleventh grade of SMA Negeri 9 Makassar in term of accuracy.